-3x+7-6(x-1)=-(2x-4)-6x+6

Simple and best practice solution for -3x+7-6(x-1)=-(2x-4)-6x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x+7-6(x-1)=-(2x-4)-6x+6 equation:



-3x+7-6(x-1)=-(2x-4)-6x+6
We move all terms to the left:
-3x+7-6(x-1)-(-(2x-4)-6x+6)=0
We multiply parentheses
-3x-6x-(-(2x-4)-6x+6)+6+7=0
We calculate terms in parentheses: -(-(2x-4)-6x+6), so:
-(2x-4)-6x+6
We add all the numbers together, and all the variables
-6x-(2x-4)+6
We get rid of parentheses
-6x-2x+4+6
We add all the numbers together, and all the variables
-8x+10
Back to the equation:
-(-8x+10)
We add all the numbers together, and all the variables
-9x-(-8x+10)+13=0
We get rid of parentheses
-9x+8x-10+13=0
We add all the numbers together, and all the variables
-1x+3=0
We move all terms containing x to the left, all other terms to the right
-x=-3
x=-3/-1
x=+3

You can always share this solution

See similar equations:

| b^2+5=17 | | z?-41=54 | | 4u-36=6(u-5) | | d?698=-271 | | -216=-6(1-5r) | | x-4-15=10 | | -7y+2(y-2)=31 | | 7(n=4)21 | | 3(-4-6b)=114 | | 181=84-w | | -140=5(4a-4) | | k-875=-750 | | y=4×5+12 | | k?875=-750 | | -8q=-88 | | -m+8(5-8m)=300 | | -3t=-78 | | 6x-4(3-2x)=4(x-4)-36 | | 41=6g+5 | | -8=w/8 | | 180=(3x+8)+(2x+24) | | -7-4n=21 | | 2h?-2h?3=13 | | n?14=49 | | 6x=15+5(x) | | 5u=-90 | | 3(15–2x)=7x+12–2x | | 9w=-90 | | 1.5h=5=2 | | q+-11=-63 | | 13x-118=6x-13 | | X+2÷3=x+34÷10 |

Equations solver categories